2005
DOI: 10.1177/107769900508200108
|View full text |Cite
|
Sign up to set email alerts
|

Latino Representation on Primetime Television

Abstract: This study analyzes the frequency and quality of depictions of Latinos during the 2002 primetime television season. Research on cultivation theory and social identity theory provides insight into the potential implications of exposure to these images. Findings suggest that while advances have been made in terms of the quality of depictions of Latinos, many of these images remain tied to a few, longstanding media stereotypes. In addition, the rate at which Latinos are portrayed on television remains dramaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(134 citation statements)
references
References 16 publications
(2 reference statements)
9
120
0
5
Order By: Relevance
“…Content analytic research has consistently demonstrated that the media often adhere to traditional gender stereotypes in the presentation of men and women (Dietz 1998;Glaubke et al 2001;Mastro andBehm-Morawitz 2005: Signorielli 1989;Signorielli and Bacue 1999;Signorielli and Kahlenberg 2001). Eagly (1987) argues that such culturally transmitted gender stereotypes influence individuals' gender role beliefs and behaviors.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Content analytic research has consistently demonstrated that the media often adhere to traditional gender stereotypes in the presentation of men and women (Dietz 1998;Glaubke et al 2001;Mastro andBehm-Morawitz 2005: Signorielli 1989;Signorielli and Bacue 1999;Signorielli and Kahlenberg 2001). Eagly (1987) argues that such culturally transmitted gender stereotypes influence individuals' gender role beliefs and behaviors.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Los resultados de este estudio son convergentes con los realizados en estas áreas y con estudios previos desarrollados en Estados Unidos en relación con la representación de las minorías étnicas en la ficción televisiva (Mastro y Greenberg, 2000;Mastro y Behm-Morawitz, 2005) y con un estudio 17 realizado por Igartua, Barrios y Ortega (2012).…”
Section: Conclusionesunclassified
“…On English-language prime-time television programs, Latino characters are more likely than characters of other ethnic groups to be cast as having low-status occupations, including being four times as likely to portray domestic workers than any other ethnic group and having lower job authority than European-American characters (Children Now 2004;Mastro and Behm-Morawitz 2005). In addition, African-Americans and Latinos are more often represented in stories related to crime and more likely to be portrayed as lawbreakers than victims in news stories (Children Now 2004;Dixon and Linz 2000;Mastro and Behm-Morawitz 2005;Mastro and Greenberg 2000). African Americans were found to be more likely to be provocatively dressed, were less professional, and were more likely to be lazy and ridiculed on prime-time TV (Mastro and Greenberg 2000).…”
Section: Gender and Race Portrayals On English-language Televisionmentioning
confidence: 99%